2021
DOI: 10.1038/s41598-021-90418-w
|View full text |Cite
|
Sign up to set email alerts
|

Heritable variation in swimming performance in Nile tilapia (Oreochromis niloticus) and negative genetic correlations with growth and harvest weight

Abstract: Nile tilapia is predominantly produced in smallholder ponds without aeration. We hypothesize that Nile tilapia with high oxygen uptake efficiency (O2UE) may perform better under these conditions than Nile tilapia with low O2UE. Critical swimming speed (Ucrit, in cm s−1) is a potential indicator for O2UE. Our objectives were to estimate variance components for Ucrit and fish size at swim testing early in life, and genetic correlations (rg) between Ucrit with harvest weight (HW) and daily growth coefficient (DGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…Genetic covariance might be expected as the result of a fitness tradeoff between growth and swimming performance (Billerbeck et al, 2001 ; Ghalambor, 2003 ), or selection on groups of traits as a dispersal syndrome: e.g., in Anolis lizards (Calsbeek & Irschick, 2007 ). However, our result generally agrees with other quantitative genetic studies that have sought to measure a genetic relationship between size and/or growth and swimming speed in young aquatic and marine organisms (Hilbish et al, 1999 ; Watkins & McPeek, 2006 but see Mengistu et al, 2021 for a counterexample in aquacultured Nile tilapia). The lack of phenotypic covariance measured in our study might seem to be at odds with the robust positive relationship between size and swimming speed that has been established for larval fishes (Leis, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…Genetic covariance might be expected as the result of a fitness tradeoff between growth and swimming performance (Billerbeck et al, 2001 ; Ghalambor, 2003 ), or selection on groups of traits as a dispersal syndrome: e.g., in Anolis lizards (Calsbeek & Irschick, 2007 ). However, our result generally agrees with other quantitative genetic studies that have sought to measure a genetic relationship between size and/or growth and swimming speed in young aquatic and marine organisms (Hilbish et al, 1999 ; Watkins & McPeek, 2006 but see Mengistu et al, 2021 for a counterexample in aquacultured Nile tilapia). The lack of phenotypic covariance measured in our study might seem to be at odds with the robust positive relationship between size and swimming speed that has been established for larval fishes (Leis, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…In many fishes, mortality in larval and juvenile stages is extremely size selective (Perez and Munch, 2010) suggesting that TGP should increase offspring survival to maturity. However, we recognize that rapid juvenile growth may have tradeoffs with other aspects of performance in fishes, such as swimming speed, behavioral aggression, and somatic energy storage (Schultz and Conover, 1997;dos Santos Schmidt et al, 2021;Mengistu et al, 2021;Monnet et al, 2021). In light of possible growth-fecundity trade-offs, we also examined the impacts of TGP on GSI.…”
Section: Growth Rate 21 Daysmentioning
confidence: 99%
“…It therefore is reasonable to state that Ucrit is strongly positively correlated to fitness. A previous study from our group (Mengistu et al, 2021) based on pedigree information, showed the existence of additive genetic variance for Ucrit in Nile tilapia, and a favorable genetic correlation between Ucrit and body weight, standard length, height and surface area at swimming test.…”
Section: Introductionmentioning
confidence: 76%
“…The fish were acclimatized for one hour in the swimming flume without flow. The critical swimming test was executed using a Brett type rectangular oval shape raceway with a swimming compartment on one side and a propellor for inducing flow on the other side as described by Mengistu et al (2021). In short, the swim flume measured 230 cm in length and 90 cm in width with a water depth of 40 cm, and was equipped with a Minn Kota Terrova 80 lbs propeller.…”
Section: Experimental Design and Traits Collectionmentioning
confidence: 99%
See 1 more Smart Citation